Quantitative EEG in schizophrenia and depression - Begić, Dražen (Array, 2009)
Introduction: Quantitative EEG (qEEG) has yielded different results in schizophrenia and depression. Since there have been few research attempts comparing patients with schizophrenia and depression using the qEEG parameters, the aim of the present research is to conduct such a comparison. Method. Three groups of subjects were included in study: experimental group I consisting of 30 patients with schizopfrenia, experimental group II consisting of 34 patients with depression and a control group with 30 healthy subjects. The diagnoses were established according to the DSM-IV criteria. EEG was recorded from Fp1, Fp2, F3, F4, F7, F8, T3, T4, P3, P4, O1 and O2 regions. The Fast Fourier Transformation (FFT) method was used to analyse a 10 second period, artifact free. The resuls are presented in the form of spectral power (µ ; ; V² ; ; ) for a particular segment of the EEG spectrum (delta, theta, alpha and beta). Results: Results indicate a difference between schizophrenia and depression in the slow rhythms (especially over the frontal regions). Furthemore, in comparison to patients with diagnosed depression, the results indicate a global decrease in alpha activity among patients with diagnosed schizophrenia. Patients were found to differ from healthy subjects in delta, theta and beta rhythms. Conclusions: These results were compared and interpreted in the context of the neuroradiological and neurotransmitter studies of schizophrenia and depression, thus confirming the biological foundation of schizophrenia and depression. Delta and theta rhythms may play a role as a marker in differentiating between schizophrenia and depression.